PENGARUH KUALITAS PELAYANAN JASA DAN CITRA PERGURUAN TINGGI TERHADAP KEPUASAN MAHASISWA DENGAN WORD OF MOUTH SEBAGAI VARIABEL INTERVENING - Baskoro Sri Widodo Putro, Rahayu Triastity & Suprihatmi Sri Wardiningsih (Universitas Slamet Riyadi, 2017)
The purpose of this study are: 1) To analyze the significance of the influence of the quality of service and the image of the college to the word of mouth in the Student Faculty of Economics Unisri Surakarta. 2) To analyze the significance of the influence of service quality, the image of the college, and word of mouth to satisfaction of students in the Student Faculty of Economics Unisri Surakarta. 3) To analyze the significance of the influence of the quality of service and the image of the college to the student satisfaction mediated by word of mouth at the Faculty of Economics Unisri Surakarta. The research method used survey method, the type of data used quantitative and qualitative data, the data source used primary data and secondary data. The population in this study Faculty of Economics Unisri force Surakarta years 2013-2015, as many as 803 students. The number of samples in this study were 80 respondents, the sampling technique using proportional cluster random sampling. Data collection methods used: questionnaire, observation and documentation. Data analysis technique used to test the validity, reliability test, classic assumption test, path analysis. Based on the results obtained conclusions: 1) There is a significant effect on the quality of service word of mouth at the Faculty of Economics Unisri Surakarta. 2) There was a significant effect on the image of the college of word of mouth in the Student Faculty of Economics Unisri Surakarta. 3) There is significant influence service quality to satisfaction of students in the Student Faculty of Economics Unisri Surakarta. 4) There is a significant influence on the image of college student satisfaction in the Student Faculty of Economics Unisri Surakarta in force from 2013 to 2015. 5) There was a significant effect of word of mouth to satisfaction of students in the Student Faculty of Economics Unisri Surakarta. 6) The results of the analysis we concluded that the indirect effect of service quality on student satisfaction mediated significant word of mouth. 7) The results of the analysis we concluded that the indirect effect on the image of college student satisfaction mediated significant word of mouth.Keywords: quality of service, the image of the college, word of mouth, student satisfaction